A Study to Compare the Kinematic Chain Exercise Versus Theraband Exercise on Pain for Subjects with Flat Foot. - S., Precilla Priyadharshini; Kamalakannan M.; J. P., Andrew Anbarason; Anitha A.; Ramana K. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: Pes Planus (flatfoot) only becomes a medical issue when symptoms appear. This disease occurs in both young children and adults. When the medial longitudinal arch (MLA) has raised to the point where it cannot be maintained, the flatfoot changes form. This condition causes over pronation of the foot in contrast to normal feet, resulting in heel eversion and moving the weight load inward to compress the MLA.1-2 Purpose: To compare the effectiveness of kinematic chain exercise and TheraBand exercise session among the young adults with flat foot. Materials and Methods: 30 subjects participated and were taken from Saveetha college of physiotherapy based on specific criteria and assigned to two groups. Pre and post assessment was taken using Numerical Pain Rating Scale [NPRS] and Foot Functional Index Scale [FFI]. The interventions were given for 2 Weeks and the study was conducted from November 2022 to April 2023. Results: The study's results revealed that both groups exhibited significant improvements in flat foot, with a p-value < 0.001. However, Group A showed more statistical significance than Group B. Conclusion: In conclusion, the commencement of two- week intervention plan, kinematic chain exercise showed a marked outcome on pain subjects with flat foot